1982
DOI: 10.1111/j.1476-5381.1982.tb08763.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Actions on Rabbit Nodal, Atrial, Purkinje Cell and Ventricular Potentials of Melperone, a Bradycardic Agent Delaying Repolarization: Effects of Hypoxia

Abstract: 1 Melperone, a butyrophenone tranquillizer, caused bradycardia in vivo and in vitro. 2 Although Melperone had ax-adrenoceptor antagonist activity in the pithed rat, it was not a P-adrenoceptor antagonist, nor was it a cholinoceptor agonist.3 The bradycardic action could be attributed almost entirely to a prolongation by Melperone of action potential duration (APD) in sinus node cells, with little effect on the slow diastolic depolarization. 4 APD was prolonged by Melperone in atrial and ventricular muscle, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In vitro we found that melperone at 2.67 tIM had no effect on A-H conduction time; at higher concentrations, however, there was a small increase in A-H conduction time, which was attributed to depressed conduction in atrium and His bundle rather than in the A-V node itself (Millar & Vaughan Williams, 1982a). However, at the lower concentrations, below the threshold for class 1 action, it has been suggested that melperone may actually reduce inactivation of sodium channels.…”
Section: Discussionmentioning
confidence: 83%
“…In vitro we found that melperone at 2.67 tIM had no effect on A-H conduction time; at higher concentrations, however, there was a small increase in A-H conduction time, which was attributed to depressed conduction in atrium and His bundle rather than in the A-V node itself (Millar & Vaughan Williams, 1982a). However, at the lower concentrations, below the threshold for class 1 action, it has been suggested that melperone may actually reduce inactivation of sodium channels.…”
Section: Discussionmentioning
confidence: 83%
“…The effects of antiarrhythmic drugs in vivo are affected by their actions on the autonomic tone, the inotropic state of the heart, and the state of the central nervous system, as well as their direct antiarrhythmic actions. The postsynaptic aadrenoceptor antagonism (Petersen, 1981), the positive inotropism (Smiseth et al, 1981;Platou et al, 1982) and the bradycardic effect of melperone (Millar & Vaughan Williams, 1982) might favourably affect the direct antiarrhythmic actions of melperone, studied in our experiments.…”
Section: Right Ventriclementioning
confidence: 94%
“…Melperone was proposed as one of the promising class 3 antiarrhythmic drugs by Vaughan Williams (Millar & Vaughan Williams, 1982). The reported serum concentrations of melperone ranged from 0.2pm to 2.0Mm during clinical administration (Refsum et al, 1978).…”
Section: Right Ventriclementioning
confidence: 99%
See 2 more Smart Citations